Les sociétés de construction au Canada avant 1867 : préliminaires à une analyse - Moscovitch, Allan (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThe author examines the forces that led to the creation of building societies in Canada. The rationale, functions and evolution of these credit institutions are examined through the experience of the Canada Permanent.